Metal ions binding by chelating ligands from new polymer bearing amidoxime functional groups - Lutfor, M.R.; Silong, S.; Wan Yunus, W.M.Z.; Rahman, M.Z.A.; Ahmad, M.B.; Haron, M.J. (SAGE Publications, 2000)
A new polymer bearing amidoxime chelating resin was prepared from polyacrylonitrile (PAN) grafted sago starch and the significant binding capacity of metal ions by the resin was observed with a rapid sorption rate.